Integrating ESG and Organizational Dimensions : A Comprehensive Model for Overall Corporate Performance Assessment - MOUFID, Ismail; BENBBA, Brahim (Revue du contrôle, de la comptabilité et de l’audit, 2024)
Corporate performance evaluation is a critical practice that plays a significant role in monitoring an organization’s effectiveness and ensuring its success, competitiveness, and long-term sustainability. Traditionally, performance assessments have relied heavily on organizational and economic-financial metrics. However, the evolving expectations of stakeholders have prompted a shift towards a more comprehensive understanding of corporate performance, leading to the development of the concept of Overall Corporate Performance (OCP). This new framework incorporates not only traditional financial indicators but also integrates environmental, societal, and governance (ESG) dimensions. In this article, we present a novel operational and combinatorial model that merges ESG factors with internal organizational dimensions. This model aims to facilitate a holistic evaluation of OCP, adopting an integrated and balanced approach. By explicitly identifying key performance indicators (KPI’s), key risk indicators (KRI’s), and key compliance indicators (KCI’s), we provide a structured methodology for quantifying and measuring performance across the various dimensions of the model. This comprehensive evaluation framework allows organizations to assess their Overall Corporate Performance in a manner that reflects both their financial health and their commitment to sustainable practices. The proposed model not only enhances the understanding of corporate performance but also aligns with contemporary trends emphasizing the importance of ESG criteria in business operations. By doing so, it addresses the growing demand from stakeholders for transparency and accountability in corporate governance. The integration of these dimensions into performance evaluation is essential for organizations aiming to thrive in today’s complex business environment, where social responsibility and environmental stewardship are increasingly prioritized alongside financial success. Corporate performance evaluation is a critical practice that plays a significant role in monitoring an organization’s effectiveness and ensuring its success, competitiveness, and long-term sustainability. Traditionally, performance assessments have relied heavily on organizational and economic-financial metrics. However, the evolving expectations of stakeholders have prompted a shift towards a more comprehensive understanding of corporate performance, leading to the development of the concept of Overall Corporate Performance (OCP). This new framework incorporates not only traditional financial indicators but also integrates environmental, societal, and governance (ESG) dimensions. In this article, we present a novel operational and combinatorial model that merges ESG factors with internal organizational dimensions. This model aims to facilitate a holistic evaluation of OCP, adopting an integrated and balanced approach. By explicitly identifying key performance indicators (KPI’s), key risk indicators (KRI’s), and key compliance indicators (KCI’s), we provide a structured methodology for quantifying and measuring performance across the various dimensions of the model. This comprehensive evaluation framework allows organizations to assess their Overall Corporate Performance in a manner that reflects both their financial health and their commitment to sustainable practices. The proposed model not only enhances the understanding of corporate performance but also aligns with contemporary trends emphasizing the importance of ESG criteria in business operations. By doing so, it addresses the growing demand from stakeholders for transparency and accountability in corporate governance. The integration of these dimensions into performance evaluation is essential for organizations aiming to thrive in today’s complex business environment, where social responsibility and environmental stewardship are increasingly prioritized alongside financial success.